Freshly Isolated Hepatocytes from Chimeric Humanized Liver Mice for the In Vitro Assessment of Drug Metabolism, Inhibition/Induction, and Safety Studies. Issue 5 (22nd May 2022) - Kakuni, Masakazu
Abstract: Human hepatocytes are a critical resource for a broad array of in vitro studies that are conducted during drug development. Cryopreserved human hepatocytes offer great advantages in terms of ease of use and lot‐specific repeatability. However, many important cell functions may be diminished or lost altogether in thawed cells. Freshly isolated human hepatocytes may provide the ideal platform for in vitro studies, but limited access to tissue, the challenges of generating high‐quality cell preparations, and the innate variability of multiple donors can all be confounding factors. Recently, freshly isolated hepatocytes from chimeric humanized mice have become available (Yamasaki et al., 2010). These PXB‐cells feature both the ease of use and lot‐specific reproducibility that is provided by cryopreserved human hepatocytes, but are freshly isolated on demand and therefore avoid the complication of diminished cellular function. PXB‐cells are prepared at a cell density of 2.1 × 10 5 cells/cm 2, delivered within 7 days post‐seeding in most of the cases, and can maintain the major drug metabolism factors at least up to 21 days post‐seeding (Yamasaki et al., 2020). © 2022 Wiley Periodicals LLC. Basic Protocol : Care and culture of PXB‐cells Support Protocol : Preparation of dHCGM medium for PXB‐cells